Selective Partner Criteria Disclosure in Post Divorce Family Communication: Pengungkapan Kriteria Pemilihan Pasangan dalam Komunikasi Keluarga Pasca Perceraian - Miranda, Vina Ayu; Subiantoro, Sumardjijati (Academia Open, 2026)
General Background: Rising divorce rates have increased attention to family communication and the interpersonal experiences of children raised by single parents. Specific Background: In post-divorce families, discussions about romantic relationships require daughters to manage privacy boundaries with their single mothers. Knowledge Gap: Limited research has examined how daughters of divorced parents regulate self-disclosure and communication privacy regarding ideal partner criteria. Aims: This study explores self-disclosure and privacy boundary management among daughters from divorced families using Communication Privacy Management Theory and Interpersonal Communication Theory. Results: Findings indicate that self-disclosure is selective, situational, and shaped by emotional readiness, perceived communication risks, and parental responses. Communication turbulence arises when parental expectations conflict with participants’ partner preferences, resulting in stricter privacy boundaries and restricted information sharing. Preferred partner characteristics include responsibility, emotional maturity, and shared religious values. Novelty: This study integrates Communication Privacy Management Theory and interpersonal communication to explain privacy boundary negotiation, boundary ownership, and communication turbulence in partner selection. Implications: The findings provide insights for promoting empathetic parent–child communication, minimizing interpersonal conflict, and supporting healthier privacy management in post-divorce families. Highlights: Emotional readiness and perceived relational risk determine personal information sharing with single mothers. Contrasting expectations between generations generate recurring communication turbulence during discussions about future relationships. Responsibility, emotional maturity, and shared religious beliefs consistently characterize preferred life partners. Keywords: Self-Disclosure, Divorce, Ideal Partner, Interpersonal Communication, Communication Privacy Management.